2006
DOI: 10.1002/jpln.200525101
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in grain cadmium concentration of lowland rice

Abstract: Cadmium (Cd) contamination of paddy rice soils is commonly observed in the Yangtse River Delta, China. Large Cd uptake by rice plants and its translocation into the grains can entail human‐health risks. Genotypic variations in Cd uptake and a differential Cd partitioning into grains will be the basis for developing a rice screening or breeding tool for low grain Cd. A field experiment, conducted at the experimental farm of Jiaxing, Zhejiang province from 2002 to 2004, compared 38 rice genotypes of different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 26 publications
7
46
1
Order By: Relevance
“…These differences in Cd concentrations may arise from the variation of Cd uptake and translocation ability of cultivar type. In similar studies, marked positive Journal of Chemistry correlations in Cd concentrations were reported between the rice roots, stems leaves, and grains [17], and marked linear correlations between Cd concentrations in rice grains and straws/roots Cd concentrations ( < 0.01) were also shown [18,19]. The results in our study further illustrated variations in Cd uptake and translocation among the five cultivars as well as organs of the same cultivar.…”
Section: Discussionsupporting
confidence: 88%
“…These differences in Cd concentrations may arise from the variation of Cd uptake and translocation ability of cultivar type. In similar studies, marked positive Journal of Chemistry correlations in Cd concentrations were reported between the rice roots, stems leaves, and grains [17], and marked linear correlations between Cd concentrations in rice grains and straws/roots Cd concentrations ( < 0.01) were also shown [18,19]. The results in our study further illustrated variations in Cd uptake and translocation among the five cultivars as well as organs of the same cultivar.…”
Section: Discussionsupporting
confidence: 88%
“…The range in SOM, clay, and CEC within each field is limited as is indicated by the low standard deviation (Table 1). Ranges in soil properties measured here are comparable to those measured by others in rice paddy fields (He et al 2006;Simmons et al 2008) 3.2 Total metal content Total metal levels vary considerably between and within fields, and they range from background levels to levels beyond current soil quality standards used in Taiwan (EPA 2006; Table 2). For the metals studied here, the number of soil samples with total metal contents in excess of the present soil monitoring values for cropped soils increases from 2.9% for Cr, 6.3% for Zn, 10.1% for Ni, 13.0% for Pb, 13.3% for Cu to 26.7% for Cd.…”
Section: Soil Properties Across the Paddy Fieldssupporting
confidence: 78%
“…This was not in agreement with the observations of many researchers that have shown a 1.5 to 3.0 times higher Cd concentration accumulating in the grains of the Indica variety compared with the Japonica variety [32] [33], which is related to the oxidizing and translocation capacity of the roots [12] [34]. Although more Cd accumulated in the roots and shoots of the Japonica variety, the accumulated Cd would not be easily transferred to the grains.…”
Section: Discussioncontrasting
confidence: 88%